PEDAGOGICAL ASPECTS OF FORMATION OF VALUABLE ATTITUDE TO HEALTH - Nevmerzhytska, Olena (Mountain School of Ukrainian Carpaty, 2020)
The article is devoted to substantiation of pedagogical aspects of formation of personal attitude to health. Current realities raise the issue of the connection between health and quality of life of a particular person and society as a whole. A person's performance of socially significant tasks or functions depends on his or her individual level of health. At the same time, the state of an individual’s health depends on the state of health of society. Although the problem of forming a valuable attitude to health is being actively developed today, the search for new ways to value the education of children and youth is always relevant. Therefore, the purpose of the article is to analyze the ways of forming a valuable attitude to health in children and youth. To achieve it, methods of analysis, synthesis, abstraction and generalization were used, which made it possible to analyze the theoretical foundations of the formation of personal values ​​of health and to formulate conclusions on improving this process. The article highlights various definitions of “health”. It is considered, in particular, as a human condition, dynamic balance of vital functions of the body, the body’s ability to adapt to the environment, well-being, social wealth, the key to a full life and normal functioning of the human body, means of supporting human life, etc. Naturally, health is considered as a universal higher value, which is expressed in a person’s attitude to their condition, which determines their orientations and preferences. The controversial nature of some of the definitions is mentioned. The necessity of finding new ways of forming values ​​is proved. These include, in particular, text analysis, biographical method, crystallization of values, problem solving and game method. Their value lies primarily in the fact that they allow the systematic implementation of all stages of personal value formation: discovery, understanding, recognition, acceptance, management of accepted values in the behavior, ​​and finally the creation of new values.